United Nations conference on trade and development: Handbook of world mineral trade statistics 1990 - 1995 (New York, 1997)
The book provides consistent data at the world, regional and country levels for international trade in the major non-fuel minerals and metals, from primary to semi-processed forms, for the period 1990 - 1995. It provides both quantities and values for these products. It includes a summary table on the value of world exports and imports of minerals, ores and metals by country and region, by the items of the Standard International Trade Classification as well as detailed tables concerning twenty-seven minerals and metals representing 93 per cent of the 1995 world trade of minerals and metals and non-monetary gold, and, as special tables, the valuation of the 1990 world non-fuel mineral production by commodity and country.
Keywords: geology, economic,mines and mineral resources,natural resources - economic aspects